Assessment of ecosystem resilience in Central Asia. (December 2021) - Qin, Jingxiu; Hao, Xingming; Hua, Ding; Hao, Haichao
Abstract: Climate change has a profound impact on ecosystem stability. Recent studies still have insufficient understanding of the response of vegetation to climate change, especially the response of vegetation to short-term climate anomalies. Based on normalized difference vegetation index (NDVI) and the meteorological data, this study conducted a quantitative assessment of the ecosystem resilience and resistance and analyzed the relationship between resistance, resilience and land cover. Furthermore, a new method was developed to identify ecologically fragile regions. The result showed that the resilience and resistance of the Central Asia ecosystem to short-term climate change are generally low. The relationship between resistance, resilience and vegetation cover was nonlinear. If there were too many or too few trees, the stability of the ecosystem was compromised. Ecologically fragile areas were found in transition areas from vegetation to non-vegetation. This study helps to better understand and quantify vegetation resilience and resistance while explicitly taking short-term climate anomalies into account. The results provide more detailed guidelines for strengthening ecosystem management. Highlights: Quantitative assessment of vegetation resilience and resistance to short-term climate anomalies in Central Asia. Non-linear relationship between vegetation resilience, resistance and vegetation cover. A new method to identify ecologically fragile regions.